2021
DOI: 10.1021/jacs.1c03427
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Conjugation of a Macrocyclic Cobalt Complex Enhances Nitrite Electroreduction to Ammonia

Abstract: This work reports on the generation of a graphiteconjugated diimine macrocyclic Co catalyst (GCC-CoDIM) that is assembled at o-quinone edge defects on graphitic carbon electrodes. X-ray photoelectron spectroscopy and X-ray absorption spectroscopy confirm the existence of a new Co surface species with a coordination environment that is the same as that of the molecular analogue, [Co(DIM)Br 2 ] + . GCC-CoDIM selectively reduces nitrite to ammonium with quantitative Faradaic efficiency and at a rate that approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 64 publications
2
53
0
Order By: Relevance
“…It is also worth noting that NO2 − is a similar nitrogen source to NO3 − for NH3 production because NO2 − is a first-step product of NO3RR and these two nitrogen oxyanions can be converted into each other in nature. Materials containing vacancies catalyze the heterogeneous six-electron NO2 − electroreduction to NH3, including Ni [450], TiO2−x [451], graphite-conjugated Co complex [452], CoP [417], Cu3P [406], Cu@JDC [453], Te-doped Pd [454], ITO/TiO2 [455], and Ag@NiO [456]. In fact, in terms of NH3 generation, both NO2 − and NO3 − are more advantageous nitrogen sources than N2 because they possess (i) lower bond breakage energy (204 vs. 941 kJ•mol −1 ), (ii) superior solubility, and (iii) higher toxicity.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 99%
“…It is also worth noting that NO2 − is a similar nitrogen source to NO3 − for NH3 production because NO2 − is a first-step product of NO3RR and these two nitrogen oxyanions can be converted into each other in nature. Materials containing vacancies catalyze the heterogeneous six-electron NO2 − electroreduction to NH3, including Ni [450], TiO2−x [451], graphite-conjugated Co complex [452], CoP [417], Cu3P [406], Cu@JDC [453], Te-doped Pd [454], ITO/TiO2 [455], and Ag@NiO [456]. In fact, in terms of NH3 generation, both NO2 − and NO3 − are more advantageous nitrogen sources than N2 because they possess (i) lower bond breakage energy (204 vs. 941 kJ•mol −1 ), (ii) superior solubility, and (iii) higher toxicity.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 99%
“…In this context, a graphite-conjugated diimine macrocyclic Co catalyst (GCC-CoDIM) assembled at o -quinone edge defects on graphitic carbon electrodes was developed for nitrite electroreduction. 80 X-Ray photoelectron spectroscopy and X-ray absorption spectroscopy confirmed that the molecular structure of the cobalt ion in GCC-CoDIM was consistent with [Co(DIM)Br 2 ] + (Fig. 10a–c).…”
Section: Electrochemical Reduction Of Nitrite To Liquid Productsmentioning
confidence: 55%
“…[7] On the other hand, however, it's difficult for homogeneous molecular catalysts to drive multielectron and multistep catalytic reduction of CO 2 due to the difficulty in trapping multiple electrons during the shuttle process. [8] Worst of all, their practical application is hindered by poor stability, bad recyclability and diffusion-dependent kinetics. [9] Integrating molecular catalysts into supports or matrixes is expected to address aforementioned issues.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, two main advantages of homogeneous catalysis are presented: i) water‐ or proton‐induced catalyst degradation and/or competitive hydrogen evolution reaction (HER) are minimized; [6] ii) reaction intermediates are easy characterized by conventional spectroscopies, thus favoring the clarification of the reaction mechanisms [7] . On the other hand, however, it's difficult for homogeneous molecular catalysts to drive multielectron and multistep catalytic reduction of CO 2 due to the difficulty in trapping multiple electrons during the shuttle process [8] . Worst of all, their practical application is hindered by poor stability, bad recyclability and diffusion‐dependent kinetics [9] .…”
Section: Introductionmentioning
confidence: 99%